Perbedaan Kadar C-Reaktive Protein (CRP) Pada Sampel Serum dan Plasma K3EDTA Dengan Metode Imunoturbidimetri - Helniasari Helniasari; Nurhidayanti Nurhidayanti; Bastian Bastian (Universitas Muhammadiyah Surabaya, 2022)
Examination of levels of C-Reactive Protein (CRP) in the blood is one of the tests. that can detect inflammation at an early stage. C-Reactive Protein (CRP) is an inflammatory marker that is synthesized in the liver. CRP levels increase due to trauma, bacterial infection and inflammation (inflammation and tissue damage). CRP is synthesized by the liver and It released into the bloodstream for 6-10 hours after the acute inflammatory process and acute destruction. Tissue detection CRP is also one of several proteins often referred to as the acute phase and It is used to monitor changes in the acute inflammatory phase associated with many infectious and autoimmune diseases. Examination of C-Reactive Protein (CRP) used serum and plasma samples of K3EDTA. C-Reactive Protein levels were measured using the Immunoturbidimetric method. This type of research was cross sectional. The study was conducted at the Clinical Pathology Laboratory, Faculty of Science and Technology, Institute of Health Sciences and Technology Muhammadiyah Palembang on December 21, 2021 with samples were 30. The results of the study had an average value in serum samples of 6.3 mg/L and an average value in plasma. K3EDTA 6.5 mg/L. Wilcoxon test results obtained p value = 0.000. The conclusion of the study was that there were differences in the examination of C-Reactive Protein (CRP) levels in serum and plasma samples of K3EDTA using the immunoturbidimetric method.